Soft war : the ethics of unarmed conflict - Gross, Michael L., 1954-; Meisels, Tamar (Cambridge : Cambridge University Press, 2017)
Just war theory focuses primarily on bodily harm, such as killing, maiming, and torture, while other harms are often largely overlooked. At the same time, contemporary international conflicts increasingly involve the use of unarmed tactics, employing'softer' alternatives or supplements to kinetic power that have not been sufficiently addressed by the ethics of war or international law. Soft war tactics include cyber-warfare and economic sanctions, media warfare, and propaganda, as well as non-violent resistance as it plays out in civil disobedience, boycotts, and'lawfare.' While the just war tradition has much to say about'hard' war - bullets, bombs, and bayonets - it is virtually silent on the subject of'soft' war. Soft War: The Ethics of Unarmed Conflict illuminates this neglected aspect of international conflict.
Title from publisher's bibliographic system (viewed on 07 Jul 2017).
Keywords: Tactics; War -- Moral and ethical aspects